2017
DOI: 10.1016/j.carbon.2017.08.070
|View full text |Cite
|
Sign up to set email alerts
|

An understanding of lattice strain, defects and disorder in nuclear graphite

Abstract: In this study, microstructural parameters, such as lattice dimension, micro-strain and dislocation density, of different neutron-irradiated graphite grades have been evaluated using the diffraction profiles of X-ray diffraction (XRD) and the scattering profiles of Raman spectroscopy. Using Gen-IV candidate graphite samples (grade PCEA, GrafTech), subjected to neutron irradiation at 900°C to 6.6 and 10.2 dpa, and graphite samples of similar grain size and microstructure taken from the core of the British Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…However, XRD is unsuitable for probing few-layer graphene films grown on SiC substrate because it needs constructive interference of x-rays reflected from a set of parallel atomic planes. Krishna et al [18] have done a comparative study of the microstructural information extracted from the peaks of both Raman and XRD spectroscopy, and found that both techniques produced agreeable results for the graphite lattice strain and crystallite size, which proves the validity of deducing both strain and crystallite size from Raman spectra. So, Raman is used to analyze both strain and grain size in this paper.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, XRD is unsuitable for probing few-layer graphene films grown on SiC substrate because it needs constructive interference of x-rays reflected from a set of parallel atomic planes. Krishna et al [18] have done a comparative study of the microstructural information extracted from the peaks of both Raman and XRD spectroscopy, and found that both techniques produced agreeable results for the graphite lattice strain and crystallite size, which proves the validity of deducing both strain and crystallite size from Raman spectra. So, Raman is used to analyze both strain and grain size in this paper.…”
Section: Introductionmentioning
confidence: 97%
“…Both the strain and grain size in materials can be probed by XRD and Raman spectroscopy [16,17,18]. However, XRD is unsuitable for probing few-layer graphene films grown on SiC substrate because it needs constructive interference of x-rays reflected from a set of parallel atomic planes.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the exposed graphite edges in NiMo/CNF provide much abundant carbon edge defects which can be catalytic active sites during electrochemical reactions . Furthermore, amorphous phase carbon and lattice defect are also observed in the carbon fiber (green spot in Figure f red square 2) due to low CVD temperature (400 °C) . On the other hand, the parallel growth of carbon is observed for the catalyst at 600 °C (Figure h) exhibits the existence of nanotubes instead of fibers .…”
Section: Resultsmentioning
confidence: 97%
“…The XRD pattern of the unleached and leached samples exhibits the typical peaks of a highly ordered graphite . Apart from the intense and symmetrical peak assignable to the plane (002), other planes of the structure corresponding to other crystallographic directions were clearly detected (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…As for the values of < e > ,t he changes are not significant, and the values are comparable to those described for commercial graphite evaluateda lso from XRD data using other calculation methods. [38,41] When these graphite particles are deformed either by grinding [41] or irradiation with neutrons, [38] clearly significant increases are observed;t hese increases can be greater than one order-of-magnitude. As for the valueso fL c calculated by Equation (1), the one obtained for the unleached graphite, aroundt hree times that calculated for the leached graphite and MCMB, deserves attention.T he values tend to equalize when the broadening of the three reflections (00l) is exclusively associated with the crystallite size, as in Equation (2).…”
Section: Resultsmentioning
confidence: 99%